Modeling and measurement of hysteresis of ferroelectric actuators considering time-dependent behavior - Wolf, Felix; Sutor, Alexander; Rupitsch, Stefan; Lerch, Reinhard (Elsevier BV, 2010)
We present a model for the simulation of ferroelectric hysteresis loops. It is based on the Preisach operator and takes advantage of an analytic weight function for the underlying fundamental switching operators. The five independent parameters describing this weight function are determined for a discoidal piezoceramic actuator by adapting the model output to measurements of the polarization. Further hysteresis simulations, performed using the adapted model are compared to hysteresis measurements of the actuator. To consider time dependent switching behavior of the ferroelectric domains, our model is furthermore extended by a drift operator and verified by means of additional measurements. (C) 2010 Published by Elsevier Ltd.
Keywords: Preisach model; ferroelectric behavior; piezoelectric hysteresis; drift model; piezoceramic transducer